Early detection and management of symptoms using an interactive smartphone application (Interaktor) during radiotherapy for prostate cancer - Sundberg, Kay (Support Care Cancer, 2017)
PURPOSE: Patients undergoing radiotherapy for prostate cancer suffer from a variety of symptoms which influence health-related quality of life. We have developed an application (Interaktor) for smartphones and tablets for early detection, reporting and management of symptoms, and concerns during treatment for prostate cancer. The study evaluates the effect on symptom burden and quality of life when using the application for real-time symptom assessment and management during radiotherapy for localized prostate cancer. METHODS: A non-randomized controlled study was used at two university hospitals in Sweden where 64 patients constituted a control group and 66 patients made up an intervention group. The intervention group was asked to report symptoms via the application daily during the treatment as well as 3 weeks after. The EORTC QLQ-C30 and its module PR25 and the Sense of Coherence questionnaire were administered at three time points in both groups. RESULTS: The intervention group rated significantly lower levels of fatigue and nausea at the end of radiotherapy. Moreover, they had significantly less burden in emotional functioning, insomnia, and urinary-related symptoms at the end of treatment as well as 3 months later compared with the control group. In the multivariate analyses, with education and sense of coherence as covariates, the intervention group still significantly rated emotional functioning (p = 0.007), insomnia (p = 0.017), and urinary-related symptoms (p = 0.008) as better than the control group at T2. CONCLUSION: Study findings suggest that Interaktor could be an efficient mHealth tool for facilitating supportive care needs during cancer treatment.